PENYELESAIAN KREDIT MACET TERHADAP PERJANJIAN KREDIT PEMILIKAN RUMAH (KPR) DI PT. BANKTABUNGAN NEGARA CABANG PEKANBARU PADA MASA COVID-19 - Shelby Susandari; Mardalena Hanifah; Setia Putra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Home ownership loan (KPR) is one of the most popular banking products by thepublic. As one way to own a house, mortgages provide many advantages forcustomers, such as ease in paying installments and the ability to own a housequickly. However, on the other hand, mortgages also have a fairly high risk of noanperforming loan. Mortgage noan performing loan is a problem that is often facedby banking companies in Indonesia. This is caused by various factors, one of themain factors is during the Covid-19 pandemic which causes various things such asunilateral layoffs, business failures, and not carrying out credit procedures to thefullest due to lack of human resources. PT. Bank Tabungan Negara PekanbaruBranch is one of the banks that also experienced the problem of mortgage badloans. The purpose of this study was to determine the factors that cause noanperforming loan mortgages in PT.Bank Tabungan Negara Pekanbaru Branch andhow effective settlement of mortgage bad loans.This type of research is sociological, where data obtained through interviews withthe PI. Bank Tabungan Negara Pekanbaru Branch and customers who experiencenoan performing loan at Griya Sakti housing. The housing is domiciled by KPRBank BTN customers since 2014. The researchers took a sample of 8 customers tofind out the factors that cause and how the settlement of noan performing loanexperienced by these customers during the Covid-19 pandemic.The results showed that the factors causing noan performing loan mortgages inPT.Bank Tabungan Negara Pekanbaru branch, among others, are external factorson the part of customers, namely business failures, debtors or debtor spouses whoexperience layoffs, which has increased dramatically during Covid-19. in addition,internal factors from the State Savings Bank, in the form of not maximizingsupervision procedures during the Covid-19 pandemic, which caused Griya Saktihousing mortgage customers to potentially experience noan performing loan. Thesettlement made by the Bank always prioritizes credit rescue first, where the bankwill provide relief to customers to restructure with several previous considerations.The rescue must also be at an early stage and not yet at the time the customer'sstatus is declared noan performing loan, later the customer who restructures willhave a current credit status after carrying out several requirements set by the bank.